In vivo detection of HER2-positive breast cancer and sentinel lymph node metastasis using activatable ICG-conjugated Trastuzumab - Liu, Yunpeng; Isa, Mahendra; Nakajima, Takahito (Frontiers in Oncology, 2026)
Breast cancer continues to pose a significant health threat to women globally, with sentinel lymph node (SLN) metastasis playing a crucial role in treatment planning and prognosis. Conventional diagnostic techniques are invasive, lack dynamic capability, and have limited specificity. Moreover, detecting intraductal spread or microinvasion remains a challenge. Here, we utilized an activatable (quenched) fluorescence probe by conjugating indocyanine green (ICG) with the anti-HER2 antibody Trastuzumab for non-invasive detection of HER2-positive breast cancer and its sentinel lymph node metastasis. Specifically, we conjugated ICG-sulfo-EG4-OSu to Trastuzumab and purified it to obtain Trastuzumab–ICG. In vitro live-cell imaging and flow cytometry demonstrated that the conjugate bound specifically to HCC-1419-Luc (HER2-positive) cells and emitted fluorescence, whereas no fluorescence was observed in BT-20-Luc (HER2-negative) cells. Orthotopic tumor models and lymph node metastasis models further confirmed its in vivo specificity. These results indicate the potential of Trastuzumab–ICG for high-specificity detection of HER2-positive breast cancer and its lymph node metastases, offering a promising tool for high-contrast tumor visualization and personalized treatment guidance.